Potensi Daun Kayu Bawang (Protium javanicum) sebagai Penghambat Kerja Enzim Tirosinase - Irmanida Batubara; Morina Adfa (Universitas Negeri Surabaya, 2013)
Utilization of Kayu Bawang (Protium javanicum) plant is needed beside its utilization for building material, especially the utilization of the leaves which easily to get. The aim of this research was to describe the potency of Kayu Bawang leaves as tyrosinase inhibitor, an enzyme which responsible to synthesis melanin as natural color of the skin. The leaves of Kayu Bawang macerated with methanol. The methanol extract then partitioned with n-hexane, EtOAc, n-BuOH, and water. All fractions were concentrated and tested its ability to inhibit tyrosinase with two substrates namely L-DOPA (diphenolase reaction) and L-tyrosine (monophenolase reaction). The result showed that n-hexane fraction could inhibit diphenolase reaction with IC50 value of 114.2 ppm. EtOAc fraction could inhibit monophenolase reaction (IC50 834.0 ppm). Methanol extract, n-BuOH fraction, and water fraction could not inhibit tyrosinase activities. The conclusion is nonpolar and semi polar compounds in Kayu Bawang leaves could be utilized as whitening agent.